A Critical Assessment of China-Africa Relations in the Post COVID-19 Dispensation - Okeke, Charles (Eximia, 2022)
The presence of China in Africa continues to grow despite the surge and menace of the COVID-19 pandemic. The argument remains that China sees a vacuum created by the US and the EU when it comes to critical issues concerning Africa and the African people; issues such as infrastructural development, maximization of human capital and enhancement of people-to-people engagement. Recent history shows that China has been actively involved in the activities of the African people for over five decades now; this cooperation China describes as the south-south affair. Chinese companies and investments in Africa are very noticeable, with South Africa playing host to about 300,000 – 400,000 Chinese citizens, the largest concentration of Chinese people in the continent. Some scholars particularly those from the West have more often than not criticized China and its activities in Africa, describing them as anti-thesis to African growth. However, these criticisms have not in any way slowed down the relations between the two partners. . As the world battles the threats posed by the COVID-19 pandemic, China and Africa have continued to explore new ways and opportunities to maintain their healthy relations, while seeking ways to improve it amid the economic pain caused by the outbreak. This relations no doubt has come under scrutiny since the pandemic broke out and the incident widely remembered is the alleged harsh treatment meted out to Africans living in Guangzhou. Some have argued that the escapade dented the relations between the two partners, but the effects still remain open to examination. Amidst the pandemic, FOCAC went ahead in Dakar, Senegal, in November 2021 and that forum availed China and Africa the opportunity to look at yearning economic issues in the wake of the pandemic and how to address them for the advancement of the exchange between the two, going forward. During FOCAC, the Chinese government rolled out a number of novel initiatives for China-Africa engagement; these are the nine programs on health, poverty reduction and agriculture, trade promotion, investment promotion, digital innovation, green development, capacity building, cultural and people-to-people exchange, as well as peace and security. The Dakar Declaration, the Dakar Action Plan 2022-2024, the China-Africa Cooperation Vision 2035, and the Declaration on China-Africa Cooperation on Climate Change were among the four outcome documents also released during the summit. These documents buttress the strength of the China-Africa relations even as the world continues to find answers to the COVID-19 pandemic. This paper highlights the foundation of this engagement and the gains accrued hitherto, while also exposing the losses during the same time. More critically, it looks to explore new areas and opportunities for the two partners as they continue to mastermind new socio-economic initiatives for a better and long-lasting cooperation as the world continues to pursue a permanent end to the COVID-19 pandemic.